2009
DOI: 10.1186/1477-7525-7-43
|View full text |Cite
|
Sign up to set email alerts
|

Psychometric properties of the Brazilian version of the Child Perceptions Questionnaire (CPQ11–14) – short forms

Abstract: Background: The need to evaluate the impact of oral health has led to the development of instruments for measuring oral health-related quality of life (OHQoL). One such instrument is the Child Perceptions Questionnaire (CPQ 11-14 ), developed specifically for 11-to-14-year-old children. As this questionnaire was considered long (37 items), shorter forms were developed with 8 (Impact Short Form: 8 -ISF:8) and 16 items (Impact Short Form: 16 -ISF:16) to facilitate use in the clinical setting and population-based… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
148
0
7

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(173 citation statements)
references
References 23 publications
9
148
0
7
Order By: Relevance
“…Studies have shown that dental caries can influence children's quality of life. 26,27 In the present study, which is representative of the city of Belo Horizonte, in southeastern Brazil, children with untreated dental caries experienced a 41% higher impact on OHRQoL than those without untreated dental caries. This finding had already been reported in another study with 112 children aged 8 to 10 years.…”
Section: Discussionmentioning
confidence: 60%
“…Studies have shown that dental caries can influence children's quality of life. 26,27 In the present study, which is representative of the city of Belo Horizonte, in southeastern Brazil, children with untreated dental caries experienced a 41% higher impact on OHRQoL than those without untreated dental caries. This finding had already been reported in another study with 112 children aged 8 to 10 years.…”
Section: Discussionmentioning
confidence: 60%
“…The scores obtained in the AUQEI and in the short-CPQ [11][12][13][14] were compared between groups using the Kruskal-Wallis test and MannWhitney tests, as the post hoc. For the analytical tests a statistical significance level of 5% was established.…”
Section: Discussionmentioning
confidence: 99%
“…Immediately after AUQEI, the children responded, also during an interview, the short version of the Child Perception Questionnaire (short-CPQ [11][12][13][14] [10] validated for Brazilian children by Torres et al [11]. The questionnaire is composed of 16 questions to assess the impact of oral health on the quality of life.…”
Section: Hiv-infected Childrenmentioning
confidence: 99%
See 2 more Smart Citations